0802 Cyber Victimization and Depressive Symptoms: A Mediation Model Involving Sleep Quality. (12th April 2019) - Kwon, Misol; Seo, Young S; Dickerson, Suzanne S; Park, Eunhee; Livingston, Jennifer A
Abstract: Introduction: Cyber victimization on the internet and social media platforms is a unique form of peer victimization and an emerging mental health concern among adolescents who are digital natives. Although studies have explored the relationship between cyber victimization and depression, fewer have explored how sleep quality influences this association. The current study extends previous findings on cyber victimization and depressive symptoms by examining the mediating effect of sleep quality among adolescents. Methods: A community sample of adolescents ( n =801; 57% female; mean age=13.99, SD =.81) recruited via address-based sampling completed measures of Pittsburgh Sleep Quality Index; cyber aggression scale; and Center for Epidemiologic Studies Depression Scale Revised via on-line survey. Hayes' (2013) approach was used to examine whether the relationship between cyber victimization and depression would be mediated through poor sleep quality among adolescents. Results: Cyber victimization was positively associated with having depressive symptoms when controlling for adolescents' poor sleep quality, sex, and age (c' = .03, t (758) = 3.80, p < .01, CI [.01, .04]). The mediation analysis indicated a significant indirect effect of poor sleep quality in the relationship between cyber victimization and depression among adolescents ( ab = .02, bootstrapped SE = .004, bootstrapped CI [.02, .03]). Specifically, adolescents' cyber victimization led to poor sleep quality ( a = .10, SE = .02, p < .001), which also led to increased depression ( b = .26, SE = .02, p < .001). The indirect effect of cyber victimization on depression was estimated through poor sleep quality ( a*b = .10(.26) = .02). Conclusion: Adolescents who were cyber victimized were more likely to suffer from poor sleep quality, which in turn led to a higher level of depression. Understanding these inter-correlational associations supports the need to provide effective risk prevention and interventions targeting cyber victimized youths who exhibit signs and symptoms of depression and to incorporate sleep hygiene education. Support (If Any): This research was funded by R01 AA021169 awarded to Jennifer A. Livingston by the National Institute on Alcohol Abuse and Alcoholism.